Enzymatic Conversion of Biomass to Biofuels: Process Mechanisms, Enzyme Optimization, and Industrial Challenges - Sesilia Romalinda; Vita Putri Ningtyas; Adha Raihan Fahrezi (Universitas Panca Marga, 2026)
Biomass conversion to biofuels has gained significant attention as a sustainable alternative to fossil-based energy, with enzymes playing a crucial role in enhancing process efficiency and selectivity under mild operating conditions. This review article examines the roles of key enzymes, including cellulases, hemicellulases, amylases, lipases, and laccases, in lignocellulosic hydrolysis, lignin structure disruption, and lipid esterification and transesterification reactions, enabling the production of bioethanol and biodiesel under milder operating conditions with high selectivity. Comparative insights are provided to highlight the relative performance of these enzymes in terms of conversion efficiency, substrate specificity, operational stability, and tolerance to process conditions, as reported in recent studies. The review further examines enzyme optimization strategies, including immobilization techniques, protein and metabolic engineering approaches, and advanced bioreactor configurations, which have been shown to improve enzyme reusability and overall process productivity. Quantitative performance indicators reported in the literature, such as biofuel yields and conversion efficiencies, are critically analyzed to assess the feasibility of enzymatic routes compared to conventional chemical processes. Finally, key industrial challenges related to enzyme cost, stability, and scalability are discussed, along with emerging technological pathways that support the potential industrial implementation of enzymatic biomass conversion for biofuel production.